Assessment of a pharmacokinetic and pharmacodynamic interaction between simvastatin and Ginkgo biloba extracts in healthy subjects. (1st March 2013) - Dai, Ling-Ling; Fan, Lan; Wu, Hui-Zi; Tan, Zhi-Rong; Chen, Yao; Peng, Xiang-Dong; Shen, Min-Xue; Yang, Guo-Ping; Zhou, Hong-Hao
Abstract: 1. Ginkgo biloba extract (GBE) is one of the most commonly used herbal remedies worldwide. It is usually concomitantly administrated with statins to treat diseases in geriatric patients. We aim to determine the influence of GBE on the pharmacokinetics (PK) and pharmacodynamics of simvastatin, which is currently unknown. 2. An open-label, randomized, two-period, two-treatment, balanced, crossover study was performed in 14 healthy volunteers. Subjects received simvastatin 40 mg once daily, co-treated with placebo or GBE 120 mg twice daily. Each treatment was administered for 14 d, separated by a wash-out period of 1 month. Simvastatin, simvastatin acid and lipoprotein concentrations were assessed. 3. GBE administration reduced mean simvastatin area under the curve (AUC)0–24, AUC0–∞ and C max by 39% ( p = 0.000), 36%( p = 0.001) and 32% ( p = 0.002), respectively, but did not cause significant differences in simvastatin acid PK or its cholesterol-lowering efficacy. 4. GBE consumption decreased simvastatin system exposure, but did not affect simvastatin acid PK. However, we cannot rule out the possibility for a pharmacodynamic interaction between GBE and simvastatin in vivo .